Employing Educational Games in Teaching Mathematics to Low-Achieving Third-Grade Students: Perspectives of Their Teachers in UNRWA Schools in Ramallah - Jawabreh, Reem Mashhour; Nimer, Nimah Nael; Mazara, Maram Raed; Abu Sharbak, Donia Azzam; Sarsor, Rahaf Saleh (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to explore the role of employing educational games in teaching mathematics to low-achieving third-grade students from the perspective of their teachers in UNRWA schools in Ramallah. The researchers adopted a descriptive-analytical approach, and the instrument used was a questionnaire consisting of 20 statements, distributed to a random sample of 30 male and female teachers. The results indicated that teachers use educational games in teaching mathematics to a high extent, with an overall average score of 3.92. Additionally, the results affirmed the significance of employing educational games in teaching mathematics, with an average score of 4.14, indicating high level of importance. The study also revealed that there were no statistically significant differences at the significance level (α≤0.05) in the responses of the sample participants regarding the utilization of educational games in teaching mathematics to low-achieving third-grade students, as perceived by their teachers in UNRWA schools in Ramallah. These results were attributed to variables such as gender, academic qualification, and years of experience. The study recommended the necessity of utilizing educational games to address the difficulties faced by students in learning mathematics.